Pengaruh Store Environtment terhadap Purchase Intention pada Pusaka Motor Suzuki Kalibata - Dixon R. M. Simangunsong; Megan Anneta Rizkyasti (Institut Manajemen Wiyata Indonesia, 2019)
This research is motivated by the existence of problems related to the sales of Suzuki vehicles which tend to decline in the last 3 (three) years. The interview results indicate that there are still problems related to store image and store atmosphere that affect to purchase intention. This is very closelyrelated because a consumer often assesses a vehicle showroom on its first impression seen from the store image then when it is felt in the store atmosphere in the form of exterior, general interior, store layout, and interior display. The purpose of this study was to determine the effect of store image and store atmosphere on purchase intention. The research method used is quantitative and causal methods. The sampling technique uses incidental sampling method, with a total of 97 respondents. Data analysis using multiple regression analysis, t test, F test. The results of this study are store image has no effect on purchase intention. While store atmosphere influences on purchase intention. Store image and store atmosphere simultaneously significantly influence on consumer purchase intention by 80%.